A STUDY ON WORD FORMATION PROCESSES OF REGISTER USED BY DELTA 3.1.7 AIRSOFT TEAM COMMUNITY - NINGTYAS, DWI ESTI JANUARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Word Formation Processes, Register, Airsoft, DELTA 3.1.7 AirsoftTeam Register is a variation of language used in a certain community which it makes the members of the community easier in communicating. Registers are sets of language items associated with discrete occupational or social group. Language is something that constantly develops and its developments are arranged through linguistic processes, thus the result of register in this study will also be analyzed by using word formation processes. In this case, the writer is interested in studying the registers used by DELTA 3.1.7 Airsoft Team community and using Wardhaugh’s theory to conduct this study, she also used Yule’s theory to analyze the word formation processes of register used. This study focuses on three problems; (1) What registers are used by DELTA 3.1.7 Airsoft Team community?  (2) What are the meanings of  registers used by DELTA 3.1.7 Airsoft Team community? (3) What word formation processes of the registers are used by DELTA 3.1.7 Airsoft Team community?.This study uses qualitative approach to describe the registers used by DELTA 3.1.7 Airsoft Team community to answer the problems of study. It was conducted with a goal to get the description and application of register used by DELTA 3.1.7 Airsoft Team community. Furthermore, the data of this study are transcription of direct interviews with all the members. This study found 28 registers used by DELTA 3.1.7 Airsoft Team community. The register was classified into four categories of word formation processes; 1 register of coinage, 6 register of borrowing, 1 compounding and 20 register of multiple processes. Register as variation of language is used in social groups to make their communication easier with each other in a group or working area.The writer hopes that next researchers do similar research on register withdifferent techniques and objects in order to give more contribution to the study of linguistics. The next researchers are supposed to use another theory to make theirresearch more different and unique. The writer hopes that this study will be a great model to conduct deeper analysis on Sociolinguistics.